Enhancing photovoltaic hosting capacity in distribution networks by optimal allocation and operation of static var compensators - CEYLAN, OĞUZHAN (My University, 2022)
© 2022 IEEE.This paper presents a novel two-stage optimization approach for the optimal sizing of static var compensators and their operational management to maximize the photovoltaic integration capacity of distribution systems. In the first stage, the optimal locations for fixed size photovoltaic (PV) systems are determined to minimize the sum of total voltage violations. In the second phase, the size of the PV units are resized and the optimal size, number, location, and operating strategy of the SVC units are determined to maximize PV hosting capacity. In both phases, the Marine Predators algorithm is used for the solution optimization equations. The performance of the proposed approach and solution method is validated on modified 33-node and 141-node radial distribution networks. The results are discussed from the point of view of the maximum hosting capacity and compared with the Grey Wolf optimization and Whale Optimization algorithms in terms of computational performance.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Sinyal İşleme; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Signal Processing; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; Enerji Mühendisliği ve Güç Teknolojisi; Fizik Bilimleri; Elektrik ve Elektronik Mühendisliği; Energy Engineering and Power Technology; Physical Sciences; Electrical and Electronic Engineering; Distributed generation; Distribution Networks; Marine Predators Algorithm; Static VAR compensator